Gender debates in literature 1683-1701 : the Gould-Egerton and Sprint-Eugenia-Chudleigh controversies : a thesis in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Boleyn, Teresa Deirdre (Massey University, 1995)
During the late seventeenth- and early eighteenth-centuries debates about issues of gender and sexual behaviour became prominent in literary discourse. These gender debates were informed by traditions of western literature such as the classical Greeks and Romans and the Bible. In two of these debates we can see the adaptations of misogynist writings to support claims of male superiority, expressions of male desire and women's inherently evil and depraved natures. In contrast, the women reassess the traditions to make room for female equality, expression and expectations. In the work of Robert Gould, Sarah Egerton, John Sprint, "Eugenia" and Lady Mary Chudleigh, we see a crystallisation of arguments in gender debates. Each writer describes their expectations of men's and women's behaviour and voices assumptions about the sexes based on current ideologies. In the works of the women writers we can trace the development of early English feminism.
Keywords: Sex role,18th century; Women, England; Sexual ethics, 18th century; Gender debates; Early English feminism